The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1111/1755-0998.12757
|View full text |Cite
|
Sign up to set email alerts
|

A multilocus association analysis method integrating phenotype and expression data reveals multiple novel associations to flowering time variation in wild‐collected Arabidopsis thaliana

Abstract: The adaptation to a new habitat often results in a confounding between genomewide genotype and beneficial alleles. When the confounding is strong, or the allelic effects is weak, it is a major statistical challenge to detect the adaptive polymorphisms. We describe a novel approach to dissect polygenic traits in natural populations. First, candidate adaptive loci are identified by screening for loci directly associated with the adaptive trait or the expression of genes known to affect it. Then, a multilocus gen… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 42 publications
1
14
0
Order By: Relevance
“…A homogeneous pattern of subtle frequency shifts at many loci is only observed for high mutation rates. This contrasts with experience gained from breeding and modern findings from genome-wide association studies, which are strongly suggestive of an important role for small shifts with contributions from very many loci (reviewed in [1, 15, 47–49], see [12, 50, 51] for recent empirical examples). For traits such as human height, there has even been a case made for omnigenic adaptation [8], setting up a “mechanistic narrative” for Fisher’s (conceptual) infinitesimal model.…”
Section: Discussionmentioning
confidence: 80%
“…A homogeneous pattern of subtle frequency shifts at many loci is only observed for high mutation rates. This contrasts with experience gained from breeding and modern findings from genome-wide association studies, which are strongly suggestive of an important role for small shifts with contributions from very many loci (reviewed in [1, 15, 47–49], see [12, 50, 51] for recent empirical examples). For traits such as human height, there has even been a case made for omnigenic adaptation [8], setting up a “mechanistic narrative” for Fisher’s (conceptual) infinitesimal model.…”
Section: Discussionmentioning
confidence: 80%
“…Candidate gene-based association analysis revealed that major genes controlling the flowering time, FLOWERING LOCUS C (FLC), FRIGIDA (FRI), VERNALIZATION-INSENSITIVE 3 (VIN3) and CRYPTOCHROME 2 (CRY2), are associated with natural variation (Shindo et al, 2005;Balasubramanian et al, 2006;Wollenberg and Amasino, 2012). After developing a number of accessions with the SNP information, the genome-wide association of genes regulating flowering time was identified by GWAS (Atwell et al, 2010;Li et al, 2014;Sasaki et al, 2015;The 1001Genomes Consortium, 2016Zan and Carlborg, 2018). GWAS on flowering time have been conducted in various crops other than Arabidopsis, leading to the discovery of new loci associated with flowering time (maize: Bouchet et al, 2013, rice: Huang et al, 2012, barley: Muñoz-Amatriaín et al, 2014, soybean: Zhang et al, 2015b, rapeseed: Xu et al, 2015, common bean: Moghaddam et al, 2016.…”
Section: Gwas For Morphological Phenotypesmentioning
confidence: 99%
“…()), it appears that loci of large effect size in general contribute relatively little to variation, as their allele frequencies tend to be low (Flint & Mackay, ; Yang et al., ). Zan and Carlborg () present a framework for dissecting the genomic basis of a polygenic trait by integrating information from previously identified candidate loci, for example, loci significantly associated with the phenotype or with gene expression changes correlated with the phenotype. Candidate loci are then assessed for inclusion in a multilocus model using backward elimination with a relatively lenient false discovery rate threshold, given that all such loci have already been significantly associated with the trait.…”
Section: Summary Of Special Issue “Wild Gwas”mentioning
confidence: 99%
“…Candidate loci are then assessed for inclusion in a multilocus model using backward elimination with a relatively lenient false discovery rate threshold, given that all such loci have already been significantly associated with the trait. Zan and Carlborg () demonstrate the application of the new approach to understand the polygenic basis of flowering time variation in wild‐collected A. thaliana . Their analysis demonstrates the power of integrating previous evidence—for example, from previous association scans—into a dissection of the number and effect size distribution of loci contributing to a polygenic trait.…”
Section: Summary Of Special Issue “Wild Gwas”mentioning
confidence: 99%
See 1 more Smart Citation